2009
DOI: 10.1016/j.jasms.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation of isocyanate-peptide adducts using tandem mass spectrometry

Abstract: Diisocyanates are highly reactive chemical compounds widely used in the manufacture of polyurethanes. Although diisocyanates have been identified as causative agents of allergic respiratory diseases, the specific mechanism by which these diseases occur is largely unknown. To better understand the chemical species produced when isocyanates are reacted with model peptides, tandem mass spectrometry was employed to unambiguously identify the binding site of four commercially-relevant isocyanates on model peptides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…In addition to the e-amino lysine adducts, we identified several other isocyanate-modified amino acids, in line with the results published by Hettick et al [21] and Sabbioni et al [22,23]. These modifications are most likely the result of isocyanate binding to the a-amino group of N-terminal amino acids of the various keratins and constituted an almost negligible fraction of the total modified residues.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to the e-amino lysine adducts, we identified several other isocyanate-modified amino acids, in line with the results published by Hettick et al [21] and Sabbioni et al [22,23]. These modifications are most likely the result of isocyanate binding to the a-amino group of N-terminal amino acids of the various keratins and constituted an almost negligible fraction of the total modified residues.…”
Section: Resultssupporting
confidence: 90%
“…Although evidence for conjugation of isocyanates with keratins was already presented by Wisnewski et al [25] and more recently also by Nayak et al [26], no mass spectrometry data of discrete adducts were reported in these studies. Both mono-and di-adducts are predominantly formed on the e-amino group of lysine residues, in line with results published for other proteins [19,21]. Keratins have highly homologous amino acid sequences and are also abundantly present in the lung epithelium.…”
Section: Resultssupporting
confidence: 87%
“…We recently demonstrated the potential for such methods for isocyanatepeptide adducts using tandem mass spectrometry. (23) The MAbs may also be useful reagents for the development of immunoassays designed for dNCO exposure assessments.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS analysis was performed as previously described (17, 18) . Briefly, samples were brought to 45 mM ammonium bicarbonate, reduced with tributylphosphine (TBP), and alkylated with iodoacetamide (IAA) according to manufacturer’s instructions (Pierce).…”
Section: Methodsmentioning
confidence: 99%